Manjša rimska naselja na slovenskem prostoru = Minor Roman settlements in Slovenia - Gaspari, Andrej; Horvat, Jana; Lazar, Irena (Opera Instituti Archaeologici Sloveniae, 2020)
The book discusses the minor settlements that dotted the territory of present-day Slovenia in the Roman period. This geographically diverse territory was crossed by important lines of communication and divided between three large administrative units of the Roman state: Italy and the provinces of Noricum and Upper Pannonia. Twenty-six authors wrote contributions on individual settlements in a comprehensive and clear manner roughly following a common concept. The presentation of each settlement opens with its location and name in Antiquity, possible habitation traces from prehistory, mentions in ancient literary texts and documents, and recovered epigraphic evidence. The next, main part offers an overview of the archaeological remains from the Roman period: topography, infrastructure, buildings, cemeteries and portable remains of particular significance. This is followed by the information on the status of a settlement, social standing of its inhabitants, their administrative or military functions, as well as professional or ethnical background. All is brought together in an outline of the historical development of each settlement.